Analisis Perbandingan Sosial Ekonomi Desa dan Kota dalam Pembangunan Wilayah - Novida Yenny; Mulhady Putra; Amanda Anggraini; As-Syifa R Ramadhani Tanjung (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Regional development is a key strategy for enhancing community welfare. However, the dynamics of growth in each region are shaped by distinct characteristics of rural and urban areas. Rural areas face unique challenges in adapting to changing times, given their economic structures are largely dominated by agriculture and limited infrastructure. In contrast, cities tend to have more diversified economies, supported by industry, services, and better access to education and technology. The socio-economic disparities between rural and urban areas pose a significant challenge in regional development. The quality of life for communities in both regions is often affected by disparities in income, healthcare, education, and employment opportunities. Ongoing modernization and urbanization lead to transformations in social and economic structures in cities and rural areas. A comparative socio-economic analysis of rural and urban areas can provide valuable insights into how these differences impact regional development strategies. This study can also inform policies aimed at achieving balanced development between rural and urban areas, thereby promoting more equitable distribution of community welfare